Links Between Barents‐Kara Sea Ice and the Extratropical Atmospheric Circulation Explained by Internal Variability and Tropical Forcing. Issue 1 (17th January 2020) - Warner, J. L.; Screen, J. A.; Scaife, A. A.
Abstract: Changes in Arctic sea ice have been proposed to affect midlatitude winter atmospheric circulation, often based on observed coincident variability. However, causality of this covariability remains unclear. Here, we address this issue using atmospheric model experiments prescribed with observed sea surface temperature variations and either constant or time‐varying sea ice variability. We show that the observed relationship between late‐autumn Barents‐Kara sea ice and the winter North Atlantic Oscillation can be reproduced by simulated atmospheric internal variability but is not simulated as a forced response to sea ice. Observations and models suggest reduced sea ice is linked to a weaker Aleutian Low. We show that simulated Aleutian Low variability is correlated with observed sea ice variability even in simulations with fixed sea ice, implying that this relationship is not incidental. Instead, we suggest that covariability between sea ice and the Aleutian Low originates from tropical sea surface temperature and rainfall variations and their teleconnections to the extratropics. Plain Language Summary: Recent dramatic changes in Arctic sea ice due to climate change have been linked to changes in weather patterns across the Northern Hemisphere. Many studies have proposed such links, but correlation does not necessarily imply causality. Here, we explore the causality of this link using atmospheric models run with observed sea surface temperature variations and either constant or time‐varying sea ice. We find that changes in weather patterns over the Atlantic that are correlated with sea ice variations are not caused by changes in sea ice. Instead, the correlation appears to be an incidental occurrence due to internal atmospheric variability. Additionally, we find that changes in weather patterns over the North Pacific, which are also correlated with sea ice variations, are reproduced in model experiments with no knowledge of these sea ice variations. In this case, the correlation appears to arise due to a third factor: rainfall variations over the tropical Pacific Ocean, which can affect midlatitude weather irrespective of sea ice changes. Key Points: Atmospheric model experiments aid causal interpretation of links between Arctic sea ice and midlatitude winter atmospheric circulation Observed links between autumn Barents‐Kara sea ice and the winter North Atlantic Oscillation is largely explained by internal variability Observed links between autumn Barents‐Kara sea ice and the winter Aleutian Low appears to originate from tropical SST and rainfall changes